Exponential stability of a Von Karman model with thermal effects - Assia Benabdallah; Djamel Teniou (Electronic Journal of Differential Equations, 1998)
A one-dimensional Von Karman model with thermal effects is studied. We derive the equations that constitute the mathematical model, and prove existence and uniqueness of a global solution. Then using Lyapunov functions, we show that solutions decay exponentially.